DEVELOPING CREATIVE LINE DRAWING SKILLS IN ARTS FOR EIGHTH GRADERS BY INTEGRATING DAVIES’ INSTRUCTIONAL MODEL WITH LOCAL CONTEXTS - Siriburi, Thatsani; Ekkapim , Samarn (Journal for Developing the Social and Community, 2023)
The objective of this research is to develop the creative line drawing skills in visual arts works of second-year high school students by integrating Davies’ Instructional Model with local contexts. The target audience consists of 34 second-year high school students from Sahatsakhansuksa School within the Secondary Educational Service Area Office of Kalasin. The tools used in the research can be categorized into three types, which include: 1) Research operational tools, consisting of 9 learning management plans. 2) Reflective tools, including assessments of student performance behavior assessment form and interview forms. And 3) Skills assessment tools, these involved evaluation of creative line drawing skills in visual arts works. The statistical analyses used include percentages, means, and standard deviations. The research findings reveal that Students have creative line drawing skills in visual art works in all 3 cycles: In the first practice round, the average score was 43.41%. In the second practice round, the average score was 60.24%. Finally, in the third practice round, the average score was 74.59%. These results indicate that students have shown improvement in their creative line drawing skills in their visual arts, with progression corresponding to the practical round's development sequence.